Linear Growth Trajectories, Catch-up Growth, and Its Predictors Among North Indian Small-for-Gestational Age Low Birthweight Infants: A Secondary Data Analysis - Sinha, Bireshwar; Choudhary, Tarun Shankar; Nitika, Nitika; Kumar, Mohan; Mazumder, Sarmila; Taneja, Sunita; Bhandari, Nita (Frontiers in Nutrition, 2022)
Background: Low birthweight small-for-gestational-age (birthweight below the 10th percentile for gestational age; SGA-LBW) infants are at increased risk of poor postnatal growth outcomes. Linear growth trajectories of SGA-LBW infants are less studied in South Asian settings including India. Objectives: To describe the linear growth trajectories of the SGA-LBW infants compared with appropriate-for-gestational-age LBW (AGA-LBW) infants during first 6 months of life. In addition, we estimated catch-up growth (Δ LAZ >0.67) in SGA-LBW infants, and their performance against WHO linear growth velocity cut-offs. We also studied factors associated with poor catch-up growth in SGA-LBW infants. Methods: The data utilized were from an individually randomized controlled trial that included LBW infants weighing 1500-2250 grams at birth. A total of 8360 LBW infants were included. Between SGA-LBW and AGA-LBW infants, we presented unadjusted and adjusted estimates for mean differences or risk ratios for the outcomes of length, linear growth velocity, LAZ score and stunting. We estimated the proportion of catch-up growth. Generalized linear models of the Poisson family with log link were used to identify factors associated with poor catch-up growth in SGA-LBW infants. Results: SGA-LBW infants had higher risk of stunting, lower attained length, and LAZ score throughout the first 6 months of life compared with AGA-LBW infants, with the differences being maximum at 28 days and minimum at 6 months of age. The linear growth velocity in SGA-LBW infants against the AGA-LBW infants was significantly lower during birth-28 days period (MD -0.19, 95% CI: -0.28 to -0.10) and higher during the 3-6-month period (MD 0.17, 95% CI 0.06 to 0.28). Among the SGA-LBW infants 55% showed catch-up growth for length at 6 months of age. Lower wealth quintiles, high birth order, home birth, male child, term delivery, non-exclusive breastfeeding, and pneumonia were associated with higher risk of poor catch-up in linear growth among SGA-LBW infants. Conclusions: SGA status at birth independent of gestational age, is a determinant of poor postnatal linear growth. Promotion of institutional deliveries, exclusive breastfeeding and prevention and early treatment of pneumonia may be helpful to improve linear growth in SGA-LBW infants during early infancy.